Assessing of health promoting lifestyle profile among students in Universiti Utara Malaysia - Kim, Ji Fang; Mohamed Elias, Ezanee (Universiti Utara Malaysia, 2020)
Nowadays, students have different life conditions and lifestyle in a university environment as many students develop a series of unhealthy habits, such as insufficient nutrition intake, rest and exercise. Students with unhealthy lifestyle, did not take enough nutrients and low level of exercise, were more depressed and will affect their healthy body. Factors of food intake and lack of exercise among young people has been linked to health problem and obesity. Exercise is positively related to student academics. Health directly affects achievement, attendance and academic performance. In the long-run, unhealthy lifestyle will affect a student’s performance and quality of life. Hence, this research aims to study the factors influence the health problem. Total 400 undergraduate students from Universiti Utara Malaysia (UUM) were chosen as respondents. The data collected was analysed by using SPSS version 25. The finding reveals that all the variables which are unhealthy lifestyle, food intake and lack of exercise have significant relationship with health problems.